Estudio de los factores del comportamiento del consumidor en el sector gastronómico de la parroquia Puerto Jelí - Davila Guzmán, Víctor Manuel (2015)
This project explains the factors influencing tastes and preferences of the gastronomic consumer behavior in restaurants in Puerto Jelí and proposes improving restaurant services. The study begins from a bibliographic research in scientific journals and articles, and field research surveys applied to 400 consumers and 13 interviews to restaurant owners, making a statistical analysis of the results. This allowed emphasize certain behaviors of seafood consumers in the area, the main results show the way which visitors were reported by, people who usually accompany them and the way they prefer to receive information about the cuisine restaurants.